Creating awareness of plagiarism among postgraduates in a postgraduate course through a talk - Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Submitting plagiarised works at the postgraduate level is not a manifestation of a positive researcher character; yet, such an academic crime appears to be common among students. Although the crime committed may either be intentional or unintentional, the need to prevent this from happening is necessary. Hence, to curb this problem, a minor change in the course structure was made to a postgraduate course in UKM. This change was in the form of introducing a talk on plagiarism in the course activities. The talk on plagiarism was presented to the students at the beginning of the semester to create awareness of the various forms of plagiarism, the implications of plagiarism, and ways of preventing it. This talk was followed by an investigation on the students’ understanding of the subject matter through their reflective diary entries. Results show that the talk has succeeded in getting the students to understand the forms of plagiarism and ways of preventing plagiarism.